Participação nos lucros no setor bancário: a relação entre a rentabilidade bancária de bancos no Brasil e o pagamento de participação nos lucros - Nogueira, Sérgio Guimarães (2013)
Brazilian banks have been the target of numerous changes in recent years, ranging from the appropriateness of physical structure and staff, to the development of new financial products that can be competitive, through the development of data analysis technologies and information security. In this context, the cost reduction is required, as well as the increased efficiency. From the technological viewpoint, these fronts, cost reduction and increased efficiency, can be easily understood, but when it concerns the labor might seem antagonistic. How to ensure quality of care and technical knowledge, if banks have sought to restrict the number of employees, require of them a greater number of transactions in a shorter time (giving them a lower range of preparation and training) and proposed ATMs and internet banking rather than agencies? Financial incentives can be alternative, especially the profit participation plans. The present work through a resumption of theoretical concepts of motivation and remuneration, profit-sharing or results and organization of the national financial system, aims to verify that the financial results of banks can be influenced by the profit sharing paid to employees. The return on assets (ROA) was the chosen indicator to measure the bank profitability. Through a database that brings together all the commercial banks, and Caixa Econômica Federal, exist in one or more years between 2001 and 2011, and whose financial information (balance sheet-BP and statement of income for the year DRE) were available in the IFTs (Quarterly Financial Information) of the Central Bank of Brazil, has built up a model. In this model, the ROA is the dependent variable and the amount paid by way of participation in profits was one of the independent variables, along with the banking capitalization level of leverage, risk of the credit portfolio, immobilization of total assets, bank liquidity and growth of the credit portfolio. The estimation was done using the method of panel data with random effects. Also a analysis was made using the same method, but with fixed effects. The results showed that there is a positive and significant relationship between profit and ROA of banks, confirming the initial hypothesis of this research. Other findings that could be known also compared the amount distributed by the public banks, private banks and foreign banks; and the level of this influence on publicly traded banks, in private, and in those of State control.